2021
DOI: 10.7717/peerj.11763
|View full text |Cite
|
Sign up to set email alerts
|

A review of coral bleaching specimen collection, preservation, and laboratory processing methods

Abstract: Under current climate warming predictions, the future of coral reefs is dire. With projected coral reef decline, it is likely that coral specimens for bleaching research will increasingly become a more limited resource in the future. By adopting a holistic approach through increased collaborations, coral bleaching scientists can maximize a specimen’s investigative yield, thus reducing the need to remove more coral material from the reef. Yet to expand a specimen’s utility for additional analytic methods, infor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…There are currently no guidelines on appropriate fragment sizes for experimental examination of coral thermal tolerance 13 and this metric is rarely reported 52 . The coral restoration literature has suggested that larger fragments may result in greater survival 53 although this is not always the case 54 56 .…”
Section: Discussionmentioning
confidence: 99%
“…There are currently no guidelines on appropriate fragment sizes for experimental examination of coral thermal tolerance 13 and this metric is rarely reported 52 . The coral restoration literature has suggested that larger fragments may result in greater survival 53 although this is not always the case 54 56 .…”
Section: Discussionmentioning
confidence: 99%
“…In cases where invasive sampling cannot be avoided, sharing samples with other researchers can reduce the need for additional specimen collection ( 54 ). If lethal sampling is required, aquatic invertebrates should be euthanized prior to sampling.…”
Section: Opportunity 2: Development Of Less Invasive Sampling Methods...mentioning
confidence: 99%
“…Between 2014 and 2021 over 20,000 coral specimens and samples were collected for bleaching studies ( McLachlan et al, 2021 ), many of which are suitable for additional analyses that could address new questions concerning various aspects of bleaching. The technology and methods commonly used in coral biology research have quickly progressed in recent decades ( Cziesielski, Schmidt-Roach & Aranda, 2019 ; Grottoli et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Integration of these approaches thus allows individual specimens to be used for multiple downstream applications and expands the potential utility of every coral sample collected. Despite this, scientists and practitioners tend to sample, preserve, and archive specimens in a manner specific to their own specialized applications or aims, and on average only conduct one or two downstream analyses per study ( McLachlan et al, 2021 ). However, it is unclear how many or how often archived samples are utilized.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation